The effect of different cigarette smoking levels on gingival crevicular fluid volume and periodontal clinical parameters in Saudi Arabia - Abdullah F. AlZamil; Montaser N. AlQutub (Elsevier, 2023)
Introduction: Periodontal disease is a chronic inflammatory condition of the periodontium. It is the main cause of tooth loss and is considered one of the biggest threats to the oral cavity. Tobacco smoking has long been associated with increased risk for periodontal, peri-implant, and other medical diseases. Objective: To evaluate the effect of smoking and its level on periodontal clinical parameters (probing depth (PD), plaque index (PI), gingival index (GI), clinical attachment level (CAL), bleeding on probing (BOP), and the volume of gingival crevicular fluid (GCF)) in healthy and chronic periodontitis individuals. Material and Method: A total of 160 participants were recruited in the present study, who were equally divided into the following five groups: healthy controls (C), healthy smokers (HS), nonsmokers with periodontitis (PNS), light smokers with periodontitis (PLS), and heavy smokers with periodontitis (PHS). GCF volume and periodontal clinical parameters (PD, PI, GI, CAL, and BOP) were assessed for each participant and compared between the study groups. Result: There was a statistically significant difference in PD, PI, GI, CAL, and BOP between healthy and periodontitis patients (p < 0.001). The mean PI, PD, and CAL were considerably higher in heavy smokers than light smokers and non-smokers (P < 0.001). In contrast, the mean GI and BOP were significantly lower in heavy smokers than in light smokers and non-smokers. There was a statistically significant difference in GCF between healthy and periodontitis patients (p < 0.001). The mean GCF readings were higher in heavy smokers than light smokers or non-smokers (P < 0.001). Conclusion: The present study confirms the influence of smoking on periodontal clinical parameters. Smoking was associated with increased PD, PI, CAL, and GCF readings; however, GI and BOP were decreased in smokers. The number of cigarettes played a key role in the volume of GCF and periodontal clinical parameters.